Estrés laboral y calidad del sueño en personal asistencial del área de emergencia del mayor nosocomio de Cajamarca. - Coba Villán, N.S. (2023)
Objectives: determine the relationship between work stress and sleep quality in the care personnel of the Emergency area of the Hospital of Greater Complexity of Cajamarca in the year 2024. Methods: the study had a quantitative approach, non-experimental, cross-sectional and non-correlational design. The sample was made up of 118 members of health personnel to whom the “Pittsburgh Sleep Quality Questionnaire” and the “Stress Inventory for Health Professionals” were applied, validated with Cronbach’s alpha of 0,78 and 0,91 respectively. Results: 93 % of those surveyed presented work stress, most of which were mild; in addition, 86 % presented poor quality of sleep, of which 49 % deserve medical attention and treatment. No significant relationship was found between both variables (p = 0,132). Likewise, a significant relationship was found between profession and work stress (p =0,005). Conclusions: it was found that there is no significant relationship between work stress and sleep quality. In addition, profession was identified as a factor significantly associated with work stress in health personnel.